4 - Ex-Mineworkers and New Skills: Contradictory Perspectives of Stakeholder* - Ngcwangu, Siphelo (African Sociological Review, 2022)
* This research draws on a project which was supported by the Mining Qualifications Authority (MQA) who had contracted the Wits University REAL Centre to conduct research on a pilot project aimed at researching the challenges of finding alternative livelihood strategies for ex-mineworkers. The MQA has later expanded this project to a national level covering the various regions of mining activity in South Africa as well as labour sending areas. The pilot study was conducted in the Carletonville on the West of Johannesburg in the Gauteng Province of South Africa. The issue of skills development is placed centrally as a means of empowering ex-mineworkers to pursue alternative careers and/or to pursue means of ‘self-employment’ targeting their local economies as a primary basis to pursue such opportunities. Ex-mineworkers face crucial challenges of economic survival upon exiting employment due to retrenchment and mine closures. This paper draws on twenty-two interviews with trade unionists, an employer association and ex-mineworkers based on their experiences of undergoing various programmes meant to train them for participation in various economic activities outside of the mining sector. The research was conducted in the Carletonville area on the West of Johannesburg in the Gauteng Province of South Africa, the workers had been employed at a Gold Mine, which had closed due to prevailing economic conditions. The research concentrates on those workers who participated in a project of skills training which was run by the Mining Qualifications Authority (MQA). The findings show tensions among stakeholders in understanding the successes and failures of efforts of empowering the ex-mineworkers with new ‘portable skills’ such as bricklaying, carpentry, plumbing, painting and decorating and plastering and tilling proved inadequate to uplift them economically as the surrounding economy faced a general decline due to mine closures. The ex-mineworkers expressed concern for further employment opportunities within the sector or for training in areas that will provide economic opportunities for themselves and their families. The findings show that the optimism prevalent in South African developmental discourse on the role of skills development tends to overlook the ways in which structural conditions inform the availability of opportunities to employ the skills which people are empowered in. This aspect is not, however, a matter that has been routinely studied in the skills development literature and the paper thus calls for future research on the realities which confront ex-mineworkers.